Combatting Radicalism through Knowledge Management: A Phenomenological Study on Teachers at Raudlatul Athfal - Isnaini, Rohmatun Lukluk; Maoti, Manapiyah; Nailasariy , Asniyah (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This study investigates the utilization of knowledge management by Raudlatul Athfal (Islamic Kindergarten) teachers in combating radicalism, adopting a qualitative methodology with a phenomenological lens. It centers on the experiences of twelve certified teachers in Ikatan Guru Raudlatul Athfal (IGRA) from the Delanggu Sub-district, Klaten, Central Java, scrutinizing their strategies and perceptions through in-depth interviews, participatory observation, and documentation. The objective was to understand how teachers integrate anti-radicalism education within their pedagogical practices, emphasizing the importance of narratives, play, and interactive activities. The findings illuminate diverse interpretations of radicalism among teachers and underscore the effectiveness of collaborative efforts with parents and the community in accessing essential educational resources and further training. The study reveals a critical demand for enhancing teachers' knowledge management skills related to radicalism, advocating for targeted training programs that could significantly improve anti-radicalism education at the kindergarten level. Despite facing resource limitations, this research spotlights the potential impact of early childhood education in fostering a more tolerant and harmonious society. It suggests that upgrading educational resources, refining teacher training programs, and leveraging technology in anti-radicalism education are vital steps forward. The implications of this study are manifold, indicating the urgent need to strengthen early educators' capacity in knowledge management concerning radicalism. This supports the effective delivery of anti-radicalism education and contributes to the broader goal of nurturing a more inclusive and peaceful community. Future research should investigate the variations in teachers' perceptions of radicalism and assess the impact of knowledge management training in optimizing anti-radicalism educational strategies.